2020
DOI: 10.1007/s11097-020-09669-z
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the rhetoric of tech addiction: why we should be discussing tech habits instead (and how)

Abstract: In the past few years, we have become increasingly focused on technology use that is impulsive, unthinking, and distractive. There has been a strong push to understand such technology use in terms of dopamine addiction. The present article demonstrates the limitations of this so-called neurobehaviorist approach: Not only is it inconsistent in regard to how it understands humans, technologies, and their mutual relationship, it also pathologizes everyday human behaviors. The article proceeds to discuss dualsyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…As we have initially mentioned, there is a growing public and academic interest in internet overuse or even addiction, although the latter is highly contested. While conceptual and empirical studies on this phenomenon are emerging (see e.g., Aagaard, 2020;Büchi et al, 2019;Helsper & Smahel, 2020;Kardefelt-Winther, 2014;Sutton, 2020), an encompassing picture of how digital inequalities relate to overuse and its implications is hitherto lacking. However, recent results have shown that sections of the population deal with the abundance of ICTs in their everyday lives differently and experience digital overuse at different rates (Gui & Büchi, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As we have initially mentioned, there is a growing public and academic interest in internet overuse or even addiction, although the latter is highly contested. While conceptual and empirical studies on this phenomenon are emerging (see e.g., Aagaard, 2020;Büchi et al, 2019;Helsper & Smahel, 2020;Kardefelt-Winther, 2014;Sutton, 2020), an encompassing picture of how digital inequalities relate to overuse and its implications is hitherto lacking. However, recent results have shown that sections of the population deal with the abundance of ICTs in their everyday lives differently and experience digital overuse at different rates (Gui & Büchi, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Tracking interactions with social media elements across platforms could increase the generalizability and replicability of findings, while still drawing on behavioral data. Additionally, focusing on elements, among other factors, will force a greater emphasis on the theoretical mechanisms driving proposed relations between SMU and well-being and avoid over-pathologizing everyday behaviour [41,42].…”
Section: Shifting Away From Aggregate Usementioning
confidence: 99%
“…One direction is discourse emphasizing the biomedical model of overuse (cf. Aagaard, 2021). This discourse compares TV addiction to substance abuse and emphasizes diagnosis through symptoms that match DSM-criteria for addiction.…”
Section: Media Addiction and Disconnection Through The Arc Of Timementioning
confidence: 99%
“…People's relationship to their smartphone appears to be "fraught with ambivalences" (Ytre-Arne et al, 2020: p. 1726), as time spent on the phone is experienced as simultaneously rewarding and a waste of time. Interview studies show that people consider managing their screen time a personal responsibility (Ytre-Arne et al, 2020), and interpret failure to adequately do so as a result of their lack of self-control (Aagaard, 2021). These experiences may explain why up to a third of US parents and half of teens believe they spend too much time online (Jiang, 2018), and why half of teens and more than one in four parents in the US describe themselves as addicted to their smartphone (Felt and Robb, 2016).…”
Section: Introductionmentioning
confidence: 99%